The practitioners' path to customer loyalty: Memorable experiences or frictionless experiences?. (November 2020) - Williams, Luke; Buoye, Alexander; Keiningham, Timothy L.; Aksoy, Lerzan
Abstract: Managers of CX programs are often faced with a decision between investing more in experience design (memorable CX) or improving experience delivery (frictionless CX). Current measurement approaches in both industry and academia do not provide a useful framework to address this dilemma adequately or directly. Using 6009 brand ratings by 1070 unique respondents, this research evaluates the impact of memorable vs frictionless CX on customer share of wallet, as well as the mediating effects of satisfaction on these relationships. Both memorable and frictionless CX have significant positive effects on customer share of wallet. These effects are partially mediated by satisfaction. There is an interaction between memorable and frictionless CX which suggests that attempts to maximize both have diminishing returns. The relative impact of each type of CX varies significantly by sector. This alternative method for measuring CX and assessing its impact provides incremental insight over common industry approaches.